An exploratory research on the new curriculum design implemented in the province of Buenos Aires as from 2008. - Blanco, Sabrina (2011)
The province of Buenos Aires implemented a new curriculum design (NCD) for English Language Teaching (ELT) in 2008. This exploratory research paper attempts to assess whether both the NCD and yearly syllabus design may be considered as vehicles that foster English Linguistic Imperialism by analysing their underlying criteria and purposes. A secondary aim deals with the linkages between the language pedagogy that underlies the NCD, which seems to be mainly based on Task Based Language Teaching (TBLT), and English Linguistic Imperialism. This paper reports the results of an exploratory study of content analysis to the NCD and twenty fourth form yearly syllabus designs and interviews to five teachers of English. The analysed syllabi only include morning shift syllabi from twenty schools in San Miguel, Buenos Aires province, Argentina. The five respondents interviewed are graduated teachers of English who work at five different schools in San Miguel. Their ages range from 26 to 58 and they have from 5 to 20 years of experience. The content analysis as well as the interviews evince hidden messages implied in the proposed methodologies and purposes. These results show that the NCD and the syllabi analysed as well as TBLT serve and propel English Linguistic Imperialism in state-run schools in San Miguel, in the province of Buenos Aires.